دراسة تحليلية مقارنة للصيغ المستخدمة في حساب حجم العينة العشوائية - بشماني, شكيب (Latakia University Journal - Economic and Legal Sciences Series, 2015)
يهدف البحث إلى وضع بعض الصيغ المعبرة عن حجم العينة و توصيفها والمقارنة فيما بينها لتحديد الصيغة الأفضل من بين تلك الصيغ لحساب حجم العينة وإيجاد صيغة معدلة تعبر تعبيراً جيداً عن حجم العينة ، بالإضافة إلى تحديد حدي الاشباع الأول والثاني للصيغ ذات الصلة ووضع معادلات رياضية يمكن من خلالها التنبؤ بحجم العينة مهما بلغ حجم المجتمع . توصل الباحث من خلال دراسته إلى النتائج الآتية: - إن النتائج كانت متطابقة بالنسبة للصيغ ذات الصلة بحجم المجتمع وحجم العينة عند توحيد شروطها. - لم يزدد حجم العينة معنوياً مع زيادة حجم المجتمع عند حد الاشباع الأول . - لا توجد فروق معنوية بين حجمي العينة وفقا لحجم المجتمع عند حدي الاشباع . - توجد فروق معنوية بين حجم العينة ومتوسط إجمالي الفحص وفقاً لحجم المجتمع عند حدي الاشباع . - حصلنا على نماذج رياضية للعلاقة بين حجم المجتمع وحجم العينة وكذلك بين حجم المجتمع ومتوسط اجمالي الفحص . - توصلنا إلى وضع جدول شامل يعطينا حجم العينة المقابل لحجم المجتمع يمكن أن يكون في متناول الباحثين للاستفادة منه والاستغناء عن تطبيق الصيغ طالما هو يعتمد عليها بالأصل عند شروط معينة . The research aims to develop some formulas of sample size and characterization and comparison among themselves to determine the best formula of formulas to calculate the sample size and the creation of a modified reflected well on the sample size, in addition to specifying individual gratification I and II for the relevant formulas and mathematical equations can predict the sample size, however the size of the community. The researcher through the study the following results: The results were identical to the formula related to the size and the sample size when consolidation requirements. Sample size did not increase with increasing size of the moral community at first gratification. No moral differences between sample volume according to the size of the community when individual gratification. Moral differences exist between sample size and average total inspection according to the size of the community when individual gratification. We got a mathematical models of the relationship between size and the sample size and the size of the community and the average total inspection. We have developed a comprehensive table gives sample size corresponding to the size of the community can be accessible to researchers to take advantage of it and apply the formulas as long as it originally relied upon certain conditions.